Entrepreneurial Innovation Capability and Firm Success: An Empirical Investigation of Gem and Jewelry Businesses in Thailand - Wanitkittikul, Khotchanipa; Pratoom, Karun; Jhundra-indra, Prathanporn (วารสารการบัญชีและการจัดการ, 2019)
Entrepreneurial innovation capability enables organizations to have the ability to develop and improve new methods and processes, as well as contribute to the development or creation of products and services of businesses and stay ahead of the competitors. This study aimed to examine the effect of entrepreneurial innovation capability on firm success in gem and jewelry businesses in Thailand. The size of sample group was 127 firms. The questionnaires were used as a tool for collecting data. The statistics for this research was Multiple Regression. The result showed that entrepreneurial innovation capability in terms of firm innovativeness awareness and business risk-taking had influence on sustainable competitive advantage which in turn affecting firm success. This research developed the concepts of innovation capability and provided useful information that gem and jewelry business can take into account in order to enhance sustainable growth.